Wire arc additive manufacturing of high strength steel - Goh, Samuel Jun Wei (Nanyang Technological University, 2023)
Additive Manufacturing (AM) has been a game-changer in the manufacturing industry by enabling the creation of complex parts with high precision and reduced material waste. This technology has found applications in various industrial sectors, including aerospace, automotive, biomedical, and energy. Of the many AM processes, Wire Arc Additive Manufacturing (WAAM) has emerged as a promising technology for the fabrication of complex and large-scale metal components. This technology offers several advantages over conventional manufacturing processes, including reduced lead time, improved design flexibility, and reduced material waste. Despite its potential, there is still a need to explore and understand the properties and behavior of WAAM-fabricated components which will contribute to its development and application in various industries.